A single-cell transcriptomic atlas of all cell types in the brain of 5xFAD Alzheimer mice in response to dietary inulin supplementation - Xiaoyan Wang; Houyu Zhang; Zhou Wan; Xuetong Li; Carlos F. Ibáñez; Meng Xie (BMC Biology)
Abstract Background Alzheimer’s disease (AD) is a progressive neurodegenerative disease that is a major threat to the aging population. Due to lack of effective therapy, preventive treatments are important strategies to limit AD onset and progression, of which dietary regimes have been implicated as a key factor. Diet with high fiber content is known to have beneficial effects on cognitive decline in AD. However, a global survey on microbiome and brain cell dynamics in response to high fiber intake at single-cell resolution in AD mouse models is still missing. Results Here, we show that dietary inulin supplementation synergized with AD progression to specifically increase the abundance of Akkermansia muciniphila in gut microbiome of 5 × Familial AD (FAD) mice. By performing single-nucleus RNA sequencing on different regions of the whole brain with three independent biological replicates, we reveal region-specific changes in the proportion of neuron, astrocyte, and granule cell subpopulations upon inulin supplementation in 5xFAD mice. In addition, we find that astrocytes have more pronounced region-specific diversity than microglia. Intriguingly, such dietary change reduces amyloid-β plaque burden and alleviates microgliosis in the forebrain region, without affecting the spatial learning and memory. Conclusions These results provide a comprehensive overview on the transcriptomic changes in individual cells of the entire mouse brain in response to high fiber intake and a resourceful foundation for future mechanistic studies on the influence of diet and gut microbiome on the brain during neurodegeneration.